Activity of lysozyme on Lactobacillus hilgardii strains isolated from Port wine - Dias, Rita (2016)
This work evaluated the effect of lysozyme on lactobacilli isolated from Port wine. Bacterial growth experiments were conducted in MRS/TJ medium and inactivation studies were performed in phosphate buffer (KH2PO4), distilled water and wine supplemented with different concentrations of lysozyme. The response of bacteria to lysozyme was found to be highly strain dependent. Some strains of Lactobacillus hilgardii together with Lactobacillus collinoides and Lactobacillus fructivorans were found to be resistant to concentrations of lysozyme as high as 2000 mg/L. It was observed that among the L. hilgardii taxon the resistant strains possess an S-layer coat. Apparently, the strains of L. collinoides and L. fructivorans studied are also S-layer producers as suggested by the total protein profile obtained by SDS-PAGE. Thus, the hypothetical protective role of the S-layer against the action of lysozyme was investigated. From the various treatments used to remove the protein from the surface of the cells, the one employing LiCl (5 M) was the most effective. LiCl pre-treated cells exposed to lysozyme (2000 mg/L) in KH2PO4 buffer maintained its resistance. However, when cells were suspended in distilled water an increased sensitivity to lysozyme was observed. Moreover, it was found that the addition of ethanol (20% v/v) to the suspension medium (distilled water) triggered a strong inactivation effect especially on cells previously treated with LiCl (reduction of >6 CFU log cycles). The results suggest that the S-layer exerts a protective effect against lysozyme and that the cell suspension medium influences the bacteriolysis efficiency. It was also noted that ethanol enhances the inactivation effect of lysozyme.